Isolated Cysticercosis of Sternocleidomastoid Muscle: Role of Ultrasonography - Subash Thapa; Norman Lamichhane; Santosh Joshi (Case Reports in Infectious Diseases)
Cysticercosis is considered a common healthcare problem, especially in developing countries. The invasion of muscle by the larval stage of the pork tapeworm, Taenia solium (i.e., Cysticercus cellulosae) usually occurs in association with CNS cysts, concurrent muscle cysts, or both. Isolated skeletal muscle involvement is rare and presents with nonspecific symptoms resulting in a diagnostic dilemma for the treating physician. We report a 20-year-old female with isolated cysticercosis of right sternocleidomastoid muscle presenting as a right neck swelling and mild pain for 4 months, whose diagnosis was established by ultrasonography (USG) and computed tomogram (CT) scan. She was managed conservatively with oral albendazole therapy for four weeks resulting in complete resolution.